Transecto magnetotelúrico entre o cráton São Luís, faixa gurupi e a bacia do Parnaíba, N-NE Brasil - Uchoa, Elenilton Bezerra (2020)
The research area is located in the N-NE portion of Brazil (State of Maranhão) and encompasses the following tectonic domains: the São Luís cratonic fragment, the Gurupi Belt, the Parnaíba and São Luís basins, and Cenozoic coverings. The magnetotelluric method (MT) consists of a geophysical technique that detects natural variations of the terrestrial electric and magnetic fields to investigate the geoelectric characteristics of the subsoil. The objective of this study is to elaborate a NNW-SSE-trending MT transect of 180 km in length and 10 km in depth, to be used as a guideline to a MT campaign for the geoelectrical and geological characterization of the tectonic domains of the study area. Furthermore, correlation exercises between the São Luís (SL) and the West African (WA) cratons are proposed. The working method comprises the following steps, based on the principles of the MT method: MT instrumentation, data collection, data processing, dimensionality analysis, inversion and modeling (MT model), integration and geological interpretation. A guide including procedures and measures to be taken in a MT campaign was elaborated to aid acquisition, processing, noise removal, calculation of impedance tensors, and product development. Following this guide, an unpublished MT geophysical model was created for the São Luís cratonic fragment, the Gurupi Belt, and the Parnaíba and São Luís basins. The 2D geophysical section (TE + TM) revealed surface conductive (Parnaíba and São Luís basins and sedimentary coverings), resistive (São Luís craton), and very resistive (Gurupi mobile Belt) portions in the study area. The interpreted geological model helped identify lateral contacts between tectonic domains, cratonic limits, the lithostratigraphic adjustment in the southern portion of the section, reviving correlation exercises between the SL and WA cratons involving the Gurupi (Brazil) and the Rokelide (Liberia-Africa) belts. This study also provides a useful guide for professionals from different (mostly geoscientific) areas who intend to use the MT method for various applications. The thesis itself presents an unprecedented geophysical investigation along the São Luís cratonic fragment and the Gurupi Belt, making it possible to recognize the inner layers of the tectonic domains in the study area, as well as suggest pre-drift correlation exercises between the Brazilian and African sides.